2011
DOI: 10.3390/su3020322
|View full text |Cite
|
Sign up to set email alerts
|

The Carbon and Global Warming Potential Impacts of Organic Farming: Does It Have a Significant Role in an Energy Constrained World?

Abstract: About 130 studies were analyzed to compare farm-level energy use and global warming potential (GWP) of organic and conventional production sectors. Cross cutting issues such as tillage, compost, soil carbon sequestration and energy offsets were also reviewed. Finally, we contrasted E and GWP data from the wider food system. We concluded that the evidence strongly favours organic farming with respect to whole-farm energy use and energy efficiency both on a per hectare and per farm product basis, with the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 84 publications
4
60
0
Order By: Relevance
“…Over the last 15 years, many attempts have been made to measure the global-warming potential of conventional and diversified farming systems by calculating relative energy use, energy-use efficiency, and the outputs of key greenhouse gasses including carbon dioxide (CO 2 ), methane (CH 4 ), and/ or nitrous oxide (N 2 O) (Lynch et al 2011). In a major review of approximately 130 studies, Lynch et al (2011) analyzed farm-level energy use and global-warming potential of organic and conventional farming systems, including field, fruit, and vegetable crops, and beef, hog, poultry, and dairy production.…”
Section: Energy-use Efficiency and Reduction Of Global-warming Potentialmentioning
confidence: 99%
“…Over the last 15 years, many attempts have been made to measure the global-warming potential of conventional and diversified farming systems by calculating relative energy use, energy-use efficiency, and the outputs of key greenhouse gasses including carbon dioxide (CO 2 ), methane (CH 4 ), and/ or nitrous oxide (N 2 O) (Lynch et al 2011). In a major review of approximately 130 studies, Lynch et al (2011) analyzed farm-level energy use and global-warming potential of organic and conventional farming systems, including field, fruit, and vegetable crops, and beef, hog, poultry, and dairy production.…”
Section: Energy-use Efficiency and Reduction Of Global-warming Potentialmentioning
confidence: 99%
“…Organic agriculture is defined as having no synthetic inputs, but organic farms may or may not practise the full suite of cultivation techniques characterizing sustainable agriculture [21,25]. Although the terms 'organic' and 'sustainable' agriculture are not equivalent, studies of organic agriculture have revealed better performance than conventional systems on some (but not all) sustainability metrics, including species richness and abundance, soil fertility, nitrogen uptake by crops, water infiltration and holding capacity, and energy use and efficiency [26][27][28][29][30][31][32]. Here, we provide the most comprehensive calculation of the yield gap between organic and conventional agriculture, building on the work of others [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…This would also contribute to the profitability of these systems by reducing the costs of inputs such as pesticides [18] or managed honeybees [19]. Expanding organic and diversified practices may also enhance food security by reducing reliance on fossil fuels owing to higher energy efficiency [20] and managed honeybees through promoting wild pollinator populations [21]. At the same time, organic soils also have higher water storage and infiltration, leading to higher resilience to severe weather conditions than in conventional systems [22].…”
mentioning
confidence: 99%
“…Further, he fails to take a large-scale, systems perspective in his assertion that organic farms create more greenhouse gas emissions per unit of yield, because he considers only the gas fluxes from soils. When the entire system is considered, organic farming systems have on average higher energy efficiency and lower greenhouse gas emissions per farm product than conventional farms [20]. The lower-energy efficiency in conventional farms is primarily owing to nitrogen fertilizers, which are highly energy intensive to produce [36].…”
mentioning
confidence: 99%